Isolated relapse of multiple myeloma in the central nervous system post autologous hematopoietic stem cell transplantation: a case report and literature review - Ying Zhou; Qian Shen; Jie Zhang; Li Zhu; Qi Jiang; Xiaobing Miao (Frontiers in Oncology, 2025)
This case report retrospectively evaluated the diagnosis and treatment of a multiple myeloma (MM) patient with early relapse in the central nervous system (CNS) post autologous hematopoietic stem cell transplantation (AHSCT). We also performed a literature review of treatment options for patients with CNS myeloma. The patient was diagnosed with isolated CNS relapse of multiple myeloma one month after AHSCT, without other extramedullary lesions and with normal blood, urine, and bone marrow profiles. The patient responded better to combination therapy involving doxorubicin liposomes and a triple intrathecal injection of dexamethasone plus methotrexate plus cytarabine. However, regimens based on the daratumumab, pomalidomide, ixazomib, and selinexor failed to achieve sustained remission in this patient. Seventeen months after experiencing CNS relapse, the patient died because of disease progression. Currently, there is no standard treatment strategy for CNS myeloma and the overall prognosis is still poor.